A comparison of EU and US consumers' willingness to pay for gene-edited food: Evidence from apples. (1st April 2021) - Marette, Stéphan; Disdier, Anne-Célia; Beghin, John C.
Abstract: We compare consumers' attitude towards and willingness to pay (WTP) for gene-edited (GE) apples in Europe and the US. Using hypothetical choices in a lab and different technology messages, we estimate WTP of 162 French and 166 US consumers for new apples, which do not brown upon being sliced or cut. Messages center on (i) the social and private benefits of having the new apples, and (ii) possible technologies leading to this new benefit (conventional hybrids, GE, and genetically modified (GMO)). French consumers do not value the innovation and actually discount it when it is generated via biotechnology. US consumers do value the innovation as long as it is not generated by biotechnology. In both countries, the steepest discount is for GMO apples, followed by GE apples. Furthermore, the discounting occurs through "boycott" consumers who dislike biotechnology. However, the discounting is weaker for US consumers compared to French consumers. Favorable attitudes towards sciences and new technology totally offset the discounting of GE apples.